Year-to-year variability in haemoglobin mass response to two altitude training camps - McLean, B. D.; Buttifant, D.; Gore, C. J; White, K.; Kemp, J. (British Journal of Sports Medicine, 2013)
- Aim To quantify the year-to-year variability of altitude-induced changes in haemoglobin mass (Hbmass) in elite team-sport athletes.Methods 12 Australian-Footballers completed a 19-day (ALT1) and 18-day (ALT2) moderate altitude (~2100 m), training camp separated by 12 months. An additional 20 participants completed only one of the two training camps (ALT1 additional n=9, ALT2 additional n=11). Total Hbmass was assessed using carbon monoxide rebreathing before (PRE), after (POST1) and 4 weeks after each camp. The typical error of Hbmass for the pooled data of all 32 participants was 2.6%. A contemporary statistics analysis was used with the smallest worthwhile change set to 2% for Hbmass.Results POST1 Hbmass was very likely increased in ALT1 (3.6±1.6%, n=19; mean±~90 CL) as well as ALT2 (4.4±1.3%, n=23) with an individual responsiveness of 1.3% and 2.2%, respectively. There was a small correlation between ALT1 and ALT2 (R=0.21, p=0.59) for a change in Hbmass, but a moderately inverse relationship between the change in Hbmass and initial relative Hbmass (g/kg (R=-0.51, p=0.04)).Conclusions Two preseason moderate altitude camps 1 year apart yielded a similar (4%) mean increase in Hbmass of elite footballers, with an individual responsiveness of approximately half the group mean effect, indicating that most players gained benefit. Nevertheless, the same individuals generally did not change their Hbmass consistently from year to year. Thus, a `responder` or `non-responder` to altitude for Hbmass does not appear to be a fixed trait.